2018
DOI: 10.3892/ol.2018.8552
|View full text |Cite
|
Sign up to set email alerts
|

Screening therapeutic targets of ribavirin in hepatocellular carcinoma

Abstract: The objective of the present study was to screen the key genes of ribavirin in hepatocellular carcinoma (HCC) and provide novel therapeutic targets for HCC treatment. The mRNA expression datasets of GSE23031 and GSE74656, as well as the microRNA (miRNA) expression dataset of GSE22058 were downloaded from the Gene Expressed Omnibus database. In the GSE23031 dataset, there were three HCC cell lines treated with PBS and three HCC cell lines treated with ribavirin. In the GSE74656 dataset, five HCC tissues and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…FBXO5 has been suggested to play crucial roles in the development of HCC, cervical cancer and squamous-cell lung carcinoma in the latest research on bioinformatics analysis [46][47][48]. Also, we got the similar results in BC.…”
Section: Discussionsupporting
confidence: 63%
“…FBXO5 has been suggested to play crucial roles in the development of HCC, cervical cancer and squamous-cell lung carcinoma in the latest research on bioinformatics analysis [46][47][48]. Also, we got the similar results in BC.…”
Section: Discussionsupporting
confidence: 63%
“…In glioblastoma, anti-miR-182 expression results in increased expression of biomarkers for proliferation and stem cell biomarkers (e.g., CCNB1, CD44, Sox2, and Nestin) [45]. Xu et al reported that hsa-miR-183/CCNB1 may be related to the effect of ribavirin on HCC [46]. Therefore, we believe that the hsa-miR-182/CHL1 and hsa-miR-183/CCNB1 axes may have a strong influence on HCC pathogenesis and may provide novel therapeutic targets for HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is known to express important amounts of miR-183 18 . The Wnt/β-catenin pathway could activate miR-183 expression in HCC to promote cell invasion 19 , and miR-183 also inhibits TGF-β1-induced apoptosis in HCC tumor cells 16 .…”
Section: Resultsmentioning
confidence: 99%